PENERAPAN MODEL SAVI DALAM PEMBELAJARAN MENULIS CERPEN PADA SISWA - Chairul Bachri Bachri Siregar (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2014)
This research is motivated by shortcomings in writing short stories in particular students towrite short stories opposite of events that never happened. It was influenced by the uses of thelearning  model.  The  author  provides  an  alternative  model  of  SAVI  for  use  in  teachingwriting. However, previous authors will test the SAVI models to determine the level ofeffectiveness. Based on the research background, this study refers to some formulation of theproblem, namely: 1) How  is the  ability  of class  IX  students of  SMP  Negeri 6 Bahorok in learning to write short stories before and after the SAVI models applied in the experimentalclass; 2) How is the ability of class IX students of SMP Negeri 6 Bahorok in learning to write short  stories  without  using  SAVI  models  in  the  control  class;  3)  Is  there  a  significantdifference between the ability to write poetry class IX students of SMP Negeri 6 Bahorok inthe experimental class in the control class. The purpose of this study is to describe things that are listed in the formulation of the problem.The  underlying  theory  is  a  theoretical  model  of  SAVI  "Accelerated  Learning" presented by Dave Meier and Bobbi DePorter, that good pembelajaranyang it is learningthat involves all aspects of the senses, fun (favored students), student-centered, and can canadapt to the way into the world of students. This study used a quasi experimental researchdesign with pretest-posttest control group. The data of this research is the result of thestudents write a short story consisting of experimental classes and control classes before and after treatment. Experimental class using SAVI models, while the control class using conceptmaps. The results of this study are significant differences between the experimental classafter using SAVI models, compared with the control class using concept maps. Increasedability graders experiment (using models SAVI) by 95%, while the increase in the ability ofcontrol  class (using concept  maps)  of 68%. This  suggests that an  increase in the students 'ability to  write  short  stories in  the experimental  class is  higher than  the improvement  ofstudents' skills in writing poetry in the control class.Keywords : SAVI models, learning to write short stories